Experience moderator effect on the variables that influence intention to use mobile learning - Ayad Shihan Izkair; Muhammad Modi Lakulu (Bulletin of Electrical Engineering and Informatics, 2021)
The study has two objectives, first is exploring the variables that affect the intention to use mobile learning and second is investigating the experience moderator effect on the variables that influence intention to use mobile learning in higher education institutions (HEI) in Iraq. Then formulate a model for intention to use mobile learning. A questionnaire has been conducted in this research for collecting the feedback from the participants. The findings confirmed that social influence (SI), performance expectancy (PE), “facilitating conditions” (FCs), effort expectancy (EE) and “satisfaction” (SA) have an important influence on the intention to use mobile learning. But, this study has rejected the “personal innovativeness” (PINN) factor as it was found not important. Furthermore, the study has confirmed that the experience moderator variable has an influence of EE, SI, and PE on the intention to use mobile learning. This study is significant to the field of discipline as it will provide a roadmap for HEI to recognize the factors that affect the intention to use mobile learning.